URGENSI PENGEMBANGAN KURIKULUM PROGRAM STUDI PENDIDIKAN KIMIA UIN AR- RANIRY - Ramli Abdullah (UIN AR-RANIRY, 2014)
Urgency curriculum development education courses chemistry Faculty of Tarbiyah and Teaching UIN Ar-Raniry Banda Aceh. Implementation of this research aims to be known: (1) How is the curriculum of Chemical Education Program currently in use, and (2) How is the curriculum of Chemical Education Program that is relevant to the times now. The research was conducted at the Basic Education Program Chemistry Faculty of tarbiyah UIN Ar-Raniry Banda Aceh in April to September 2013. The method used in this research is qualitative descriptive, the population in this study is a faculty, alumni, and students of Chemistry Education Tarbiyah UIN Ar-Raniry Banda Aceh. Retrieving data using instruments interviews with faculty, students, and alumni of Basic Chemical Education Program Faculty of tarbiyah UIN Ar-Raniry Banda Aceh. While the curriculum documentation talaah Basic Chemical Education Program Faculty of tarbiyah UIN Ar-Raniry Banda Aceh and curriculum Document Basic Chemical Education Program FKIP Unsyiah Banda Aceh. The results obtained in this study are: (1) Get a picture of the curriculum of Chemical Education Program currently in use, and (2) Chemistry Education Program curriculum that is relevant to the times now for the Basic Education Program Chemistry Faculty of tarbiyah UIN Ar Raniry Banda Aceh. The conclusion of this study is mengatahui picture of Chemical Education Program curriculum currently in use, and the curriculum of Chemical Education Program are relevant to the development of today for Basic Chemical Education Program Faculty of tarbiyah UIN Ar-Raniry Banda Aceh. Suggestions put forward of this research is to improve the quality of learning in Chemistry Education Program requires continuous curriculum development, improving the quality of teachers and increase motivation and interest in students' growth Study Program Basic Chemistry Faculty of tarbiyah UIN Ar-Raniry Banda Aceh.